Confronting COVID: Crisis Leadership, Turbulence, and Self-Care - Urick, Angela; Carpenter, Bradley W.; Eckert, Jon (Frontiers in Education, 2021)
School leadership during the pandemic serves as the contextual backdrop for this conceptual article. Specifically, we believe the preparation of today's school leaders must be re-examined to consider the inclusion of frameworks that consider not only how principals might navigate extreme crises but also how they look after themselves and their wellbeing in ways that may curb the chronic stress that often leads to professional burnout. In this article, we tie together three bodies of literature – crisis management, leadership in turbulence, and self-care – and introduce a conceptual framework that may help us reconsider the preparation of today's school leader. These bodies of literature, while not yet broadly studied in education, are key to our understanding of how school leaders can successfully practice their new day-to-day practices after experiencing turmoil under the COVID-19 pandemic.